Identification of plankton species in ponds of Block O residence, Banguntapan, Bantul, Yogyakarta - Sudarsono Sudarsono (Jurnal Sains Dasar, 2014)
This research aims to identify the plankton species in the ponds of block O residence, Banguntapan, Bantul, Yogyakarta. The sample taken was accomplished by drawing 20 liters of water directly from the pond, then filtered it through the planktonnet. Field guide book of plankton identification was used to accomplish the next step, that is plankton species identification. The physicochemical condition, including temperature, turbidity, light intensity, and level of pH, were measured for every station given, and it was repeated 3 times. Shannon-Whiener equation was then used to calculate the index of diversity. This research concludes that the plankton species compositon of phytoplanton and zooplankton consist of 4 classes. They are Chlorophyceae (7 species), Cyanophyceae (7species), Bacillariophyceae (23 species), Euglenophyceae (4 species). From the total species of phytoplankton species found, around 54 species, at least 23 species are identified as the members of Bacillariophyceae, while the zooplanktons which were found in every stations consist of 4 classes, i.e. Copepod (1 species), Crustacean (2 species), Rotifer (5 species), and Protozoa (1 species). The total zooplankton species found is 10 species and 5 species of them belong to class Rotifer. The Diversity Indices on cathegoryzed in small to medium.   Key words: identification, plankton, Blok O.